Imam Ali Zainal Abidin Al-Sajjad A.S. dan Sahifah Sajjadiyyah - Muhammad Alfatih Suryadilaga (UIN Sunan Kalijaga Yogyakarta, 2011)
The article discusses words of praying in Shiite perspective found in Sahifah Sajjadiyah. The book serves as one of great references for Muslim’s religious spirituality. Besides, the Imam as a figure inspires us for his wisdom overcoming everyday problem.Among Shiite community, the author’s capacity is undoubtedly recognized for he is one of the Imams and the grand grandson of the Prophet PBUH. The book comprises of variety of praying supported a good life either in this world or in the hereafter. The pray itself implements both in daily activities in a particular time and material and natural context. In contemporary context, Sahifah Sajjadiyah becomes one of models for people’s piety in that it provides individual with rich spiritual aspects and leads a harmonize type of relationship among human beings, God and nature.